2021
DOI: 10.1007/s10803-021-05030-8
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life in Pediatric Patients with Syndromic Autism and their Caregivers

Abstract: Children with autism have a significantly lower quality of life compared with their neurotypical peers. While multiple studies have quantified the impact of autism on health-related quality of life (HRQoL) through standardized surveys such as the PedsQL, none have specifically investigated the impact of syndromic autism. Here we evaluate HRQoL in children diagnosed with three genetic disorders that strongly predispose to syndromic autism: Phelan-McDermid syndrome (PMD), Rett syndrome (RTT), and SYNGAP1-related… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 38 publications
2
13
0
Order By: Relevance
“…However, possible mediating effects of socio-economic factors should be explored in future research. Furthermore, the evidence led us to conclude that the distribution of PedsQL scores is different across PMD, SYNGAP1 -ID and RTT during the pandemic which is consistent with a previously reported finding Bolbocean et al ( 2021 ). At the same time, HRQoL scores among PMD are higher compared to the other two genetic conditions which has also been previously observed.…”
Section: Discussionsupporting
confidence: 92%
“…However, possible mediating effects of socio-economic factors should be explored in future research. Furthermore, the evidence led us to conclude that the distribution of PedsQL scores is different across PMD, SYNGAP1 -ID and RTT during the pandemic which is consistent with a previously reported finding Bolbocean et al ( 2021 ). At the same time, HRQoL scores among PMD are higher compared to the other two genetic conditions which has also been previously observed.…”
Section: Discussionsupporting
confidence: 92%
“…Motor deficits, especially gait abnormalities, are understudied, but common, phenotypes associated with neurodevelopmental disorders ( Shetreat-Klein et al, 2014 ; Colizzi et al, 2020 ). Functional physical deficits result in impaired quality of life for children with neurodevelopmental disorders including those due to monogenic lesions ( Bolbocean et al, 2022 ). Despite this, quantitative evaluations of gait are rarely performed for neurodevelopmental disorders especially as compared to frequent evaluations through neuroimaging, electroencephalography, and neurocognitive testing.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, few studies have specifically focused on the impact of caring for a child with a rare genetic disease on FQoL (Bolbocean et al, 2022; Mori et al, 2017). Mori et al (2017) investigated the FQoL among families with a child with the CDKL5 disorder and showed that the FQoL was generally lower in those using social supports such as respite care services, suggesting that these families could be more burdened by daily caregiving (Mori et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Mori et al (2017) investigated the FQoL among families with a child with the CDKL5 disorder and showed that the FQoL was generally lower in those using social supports such as respite care services, suggesting that these families could be more burdened by daily caregiving (Mori et al, 2017). Bolbocean et al (2022) evaluated FQoL among families who had children with three genetic disorders that predispose to syndromic autism: Phelan–McDermid syndrome, Rett syndrome, and SYNGAP1‐related intellectual disability. In these three conditions, emotional well‐being determined the greatest damage on FQoL; besides that, there were significant differences among the genetic disorders for parenting and family interaction, which had lower scores in the SYNGAP1‐related intellectual disability families.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation